Pelatihan Pemanfaatan Teknologi Digital Dalam Administrasi Pembelajaran di Madrasah Aliyah Al Ilham Selusuh - M Rasyid Ridlo (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of digital technology has brought fundamental changes to educational management, including the administration of learning. Learning administration that is managed effectively and supported by digital technology can improve teachers’ work efficiency, the accuracy of academic data, and the quality of educational services. However, in practice, many Islamic senior secondary schools (madrasah aliyah) have not yet optimally utilized digital technology in learning administration. This community service activity aims to enhance the competencies of teachers at Islamic Senior High School (Madrasah Aliyah) Al Ilham Selusuh in utilizing digital technology to support learning administration. The implementation method consists of needs analysis, training implementation, and continuous mentoring. The training materials focus on the use of digital applications for lesson planning, assessment management, academic documentation, and online-based archiving of learning administration. The results of the activity indicate a significant improvement in teachers’ understanding and skills in using digital technology for learning administration. Teachers are able to develop digital learning administration tools, manage learning data systematically, and improve administrative efficiency and accountability. This activity is expected to make a tangible contribution to improving the quality of learning management at Islamic Senior High School (Madrasah Aliyah) Al Ilham Selusuh. Keywords: digital technology, learning administration, teacher training, community service, Islamic Senior High School (Madrasah Aliyah)